Becoming a European Homegrown Jihadist : A Multilevel Analysis of Involvement in the Dutch Hofstadgroup, 2002-2005 - Schuurman, Bart (Book collections on Project MUSE., 2018)
How and why do people become involved in European homegrown jihadism? This book addresses this question through an in-depth study of the Dutch Hofstadgroup, infamous for causing the murder of filmmaker Theo van Gogh in 2004 and for plotting numerous other terrorist attacks. The Hofstadgroup offers a window into the broader phenomenon of homegrown jihadism that arose in Europe in 2004 and is still with us today. Utilizing interviews with former Hofstadgroup participants and the extensive police files on the group, this book overcomes the scarcity of high-quality data that has beset the study of terrorism for decades. The book advances a multicausal and multilevel understanding of involvement in European homegrown jihadism. It stresses that the factors that initiate involvement are separate from those that sustain it, which in turn are again likely to differ from those that bring some individuals to actual acts of terrorism.